2018
DOI: 10.3390/catal8110563
|View full text |Cite
|
Sign up to set email alerts
|

Promotional Effect of Gold on the WGS Activity of Alumina-Supported Copper-Manganese Mixed Oxides

Abstract: The water-gas shift (WGS) reaction is a well-known industrial process used for the production of hydrogen. During the last few decades, it has attracted renewed attention due to the need for high-purity hydrogen for fuel-cell processing systems. The aim of the present study was to develop a cost-effective and catalytically efficient formulation that combined the advantageous properties of transition metal oxides and gold nanoparticles. Alumina-supported copper- manganese mixed oxides were prepared by wet impre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…The high activity of this catalyst system makes it capable of practical usages, primarily due to economic viability as it consists of 80% alumina [118]. Sagata et al investigated the effect of aluminum oxide and the pore size of the support on the catalytic activity during the low-temperature WGS reaction over Cu catalyst [119]. They concluded that by decreasing the mesopore size of Cu/Al 2 O 3 , the catalytic activity increased only when the steam/carbon (S/C) ratio was 2.2, whereas the catalytic activity increased in the S/C ratio of 4.6 by increasing the mesopore size [119].…”
Section: Type Of Metal Oxide Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…The high activity of this catalyst system makes it capable of practical usages, primarily due to economic viability as it consists of 80% alumina [118]. Sagata et al investigated the effect of aluminum oxide and the pore size of the support on the catalytic activity during the low-temperature WGS reaction over Cu catalyst [119]. They concluded that by decreasing the mesopore size of Cu/Al 2 O 3 , the catalytic activity increased only when the steam/carbon (S/C) ratio was 2.2, whereas the catalytic activity increased in the S/C ratio of 4.6 by increasing the mesopore size [119].…”
Section: Type Of Metal Oxide Supportmentioning
confidence: 99%
“…Sagata et al investigated the effect of aluminum oxide and the pore size of the support on the catalytic activity during the low-temperature WGS reaction over Cu catalyst [119]. They concluded that by decreasing the mesopore size of Cu/Al 2 O 3 , the catalytic activity increased only when the steam/carbon (S/C) ratio was 2.2, whereas the catalytic activity increased in the S/C ratio of 4.6 by increasing the mesopore size [119]. One of the important considerations in an industrial sulfur tolerant WGS process is that the reaction conditions, not only catalysts, dictate many of the outcomes such as improvements in production capacity, decreasing production costs, and change in the catalytic activity [120,121].…”
Section: Type Of Metal Oxide Supportmentioning
confidence: 99%
“…Favorable properties of transition metal oxides and gold nanoparticles have been combined to prepare gold-based catalysts using alumina-supported Cu–Mn mixed oxides (Tabakova et al, 2018). Sample characterization by several techniques [X-ray diffraction (XRD), High-resolution transmission electron microscopy (HRTEM), Electron paramagnetic resonance (EPR), X-ray photoelectron spectroscopy (XPS), temperature-programmed reduction (TPR)] before and after WGS tests evidenced that the beneficial effect of gold promotion was related to CO activation and enhanced CuO reducibility.…”
Section: Recent Achievements In the Field Of Gold-catalyzed Wgs Reactionmentioning
confidence: 99%
“…Non-Hg organometallic catalysts, especially Au-based catalysts [3,4], have emerged with excellent catalytic performances. In recent years, great efforts have been put on exploring the high activity as well as the preparation methods for Au-based catalysts [5][6][7][8][9]. For instance, a 100% benzene conversion was achieved for the Au-based catalyst [5].…”
Section: Introductionmentioning
confidence: 99%